Go : a Kidd's guide to graphic design - Kidd, Chip (Workman Publishing, 2021)
Provides young readers with an introduction to graphic design, discussing such topics as form, typography, content, and establishing a concept. Explains which factors comprise an elegant, eye-catching design, and features full-color examples from various real-world sources throughout.